Cycloaddition Reactions of Some Tricyclic Imides - Kulu, Irem; Gul, Melek; Gunkara, Omer Tahir; Ocal, Nuket (BENTHAM SCIENCE PUBL LTD, 2013)
Our research group has published numerous papers over the last three years on the reaction of nitrile oxides and azomethine ylide with unsaturated tricyclic N-substituted dicarboximides selected according to the importance of possible biological activities. These reactions cover full range of mechanistic pathways and timings of bond-forming processes to give five-membered ring closure by 1,3-dipolar cycloaddition.
Keywords: Azomethine ylide; biological active molecules; 1,3-dipolar cycloaddition; hydrazones; isoxazolines; nitrile oxides; tricyclic imides; SUBSTITUTED CYCLIC IMIDES; HECK-TYPE HYDROARYLATIONS; 5-HT1A RECEPTOR LIGANDS; ANTIMICROBIAL ACTIVITY; IRON CHELATORS; TANDOSPIRONE; EPIBOXIDINE; AFFINITY; ANALOGS; Chemistry